Optimization of Anti-Scour Device Combined with Perforated Baffle and Ring-Wing Plate Based on a Multi-Factor Orthogonal Experiment - Yan Wang; Rongjun Liao; Pei Yuan; Jinchao Chen (Buildings)
In this paper, a new anti-scour device combined with a perforated baffle and ring-wing plate is proposed to enhance the traditional method for better protection of bridge piers from local scour. Based on computational fluid dynamics (CFD), the orthogonal experiments investigated the general laws of the influence of the main factors, such as the ratio of baffle perforated, the position of baffle, and the height of ring-wing plate on the anti-scour effect. Under the protection of the combined device, the maximum scour depth reduction rate in front of the pier is between 65.18% and 81.01%, while that at the side of the pier is between 52.63% and 68.42%. Especially when the perforated ratio is 20%, the baffle is 2d (d is diameter of the pier) away from the pier, and the ring-wing plate is located at 1/3 of water depth, the anti-scour effect is the best. Also, the flow field around the pier under the protection of the combined device is further investigated. The results show that the structure blocks the down-flow actively and diverts and dissipates the flow energy to decrease flow below the critical velocity of sediment. Thus, the device combined with perforated baffle and ring-wing plate has a prominent anti-scour effect and provides a basis for further studies and engineering application.